Mortality trends in U.S. adults with septic shock, 2005-2011: a serial cross-sectional analysis of nationally-representative data. Issue 1 (December 2016) - Goto, Tadahiro; Yoshida, Kazuki; Tsugawa, Yusuke; Filbin, Michael; Camargo, Carlos; Hasegawa, Kohei
Abstract Background We aimed to investigate mortality trends in hospitalized patients with septic shock in the US. To achieve this objective, we tested hypothesis that mortality decreased in patients identified by the code of septic shock while mortality did not change in those with septic shock identified by vasopressor use. Methods We conducted a serial cross-sectional analysis using Nationwide Inpatient Sample database from 2005 through 2011. First, we identified all adult patients aged ≥18 years hospitalized for septic shock by the following criteria: 1) primaryICD-9 diagnosis of infection plus procedure code for vasopressor use, 2) primaryICD-9 diagnosis of infection plus septic shock in non-primary field, and 3) primaryICD-9 diagnosis of septic shock. Second, we stratified all identified patients by record of vasopressor use. The outcome of interest was year-to-year changes in the in-hospital all-cause mortality. Results From 2005 to 2011, we identified 109, 812 weighted hospitalizations with septic shock. Overall, there was a significant downward trend in in-hospital mortality (from 46 % in 2005 to 42 % in 2011;P trend  = 0.003); the adjusted mortality also decreased significantly (OR for comparison of 2005 with 2011, 0.98; 95 % CI, 0.96–1.00;P  < 0.001). In stratified analysis, the mortality trend was not significant in the subgroup with vasopressor use (from 42 % in 2005 to 40 % in 2011;P trend =0.57); similarly, the adjusted mortality did not change significantly (OR, 1.01; 95 % CI, 0.97–1.05;P =0.62). By contrast, there was a downward trend in mortality in the subgroup without vasopressor use (from 47 % in 2005 to 43 % in 2011;P trend =0.002); likewise, the adjusted mortality decreased significantly (OR, 0.97; 95 % CI, 0.95–0.99;P =0.002) Conclusions From 2005 to 2011, we found a modest decrease in in-hospital mortality among patients identified with septic shock. However, in the subgroup with vasopressor use, we found no significant change in mortality. Our data challenge the conventional wisdom that mortality in this population has improved during the last decade.